Respuesta :

Answer:

[tex]b = -a +\frac{1}{4}c[/tex]

Step-by-step explanation:

Step 1: Flip the equation.

  • [tex]4a + 4b = c[/tex]

Step 2: Subtract 4a from both sides.

  • [tex]4a + 4b - 4a = c - 4a[/tex]
  • [tex]4b = c - 4a[/tex]
  • [tex]4b = -4a + c[/tex]

Step 3: Divide both sides by 4.

  • [tex]\frac{4b}{4}=\frac{-4a}{4} + \frac{c}{4}[/tex]
  • [tex]b = -a + \frac{1}{4}c[/tex]

Therefore, the answer is [tex]b = -a + \frac{1}{4}c[/tex].

Hope you have a lovely rest of your day/night.

Answer:

b = [tex]\frac{c - 4a}{4}[/tex]

Step-by-step explanation:

c = 4a + 4b

Subtract 4a from both sides:

c - 4a = 4a - 4a + 4b

c - 4a = 4b

Divide both sides by 4 to solve for b:

[tex]\frac{c - 4a}{4} = \frac{4b}{4}[/tex]

b = [tex]\frac{c - 4a}{4}[/tex]

Please mark my answers as the Brainliest if you find my solutio helpful :)